Harnessing Motivation to Alleviate Neglect - Russell, Charlotte; Li, Korina; Malhotra, Paresh A. (Frontiers in Human Neuroscience, 2013)
The syndrome of spatial neglect results from the combination of a number of deficits in attention, with patients demonstrating both spatially lateralised and non-lateralised impairments. Previous reports have hinted that there may be a motivational component to neglect and that modulating this might alleviate some of the debilitating symptoms. Additionally, recent work on the effects of reward on attention in healthy participants has revealed improvements across a number of paradigms. As the primary deficit in neglect has been associated with attention, this evidence for reward’s effects is potentially important. However, until very recently there have been few empirical studies addressing this potential therapeutic avenue. Here we review the growing body of evidence that attentional impairments in neglect can be reduced by motivation, for example in the form of preferred music or anticipated monetary reward, and discuss the implications of this for treatments for these patients. Crucially these effects of positive motivation are not observed in all patients with neglect, suggesting that the consequences of motivation may relate to individual lesion anatomy. Given the key role of dopaminergic systems in motivational processes, we suggest that motivational stimulation might act as a surrogate for dopaminergic stimulation. In addition, we consider the relationship between clinical post stroke apathy and lack of response to motivation.